(untitled) (Bioresearch Communications, 2024)
The traditional practice of ragging has been spreading towards tertiary educational institutions continuing a cycle of abuse. More often than not students of university are in the trap of ragging which is a tool of torture indeed. The present study aimed to explore the issue from the context of the University of Dhaka. The phenomenon is very pronounced but no broad-scale study has been carried out to explore student’s perception of ragging here. A cross-sectional survey design was used to capture the whole scenario. Quantitative and qualitative data were collected from 418 students of the university (58.4% male, 41.6% female) through self-responsive online questionnaire. Content analysis was adopted for analyzing qualitative data. The quantitative part was analyzed through t-test, F-test, Chi-square-test, Pearson-Product-Moment Correlation Coefficient and regression analysis via SPSS. Results found significant gender differences in students’ perception of ragging. Aggression, negative self-esteem and emotional-unresponsiveness were correlated with that perception. Findings suggested a clear lack of administrative control over the practice. Addressing the issue for ensuring a healthy educational atmosphere in the university is now a mammoth task. Bioresearch Commu. 11(1): 1741-1748, 2025 (January)